How can distinct egg polymorphism be maintained in the rufescent prinia (Prinia rufescens)–plaintive cuckoo (Cacomantis merulinus) interaction—a modeling approach. Issue 15 (15th June 2017) - Liang, Wei; Yang, Canchao; Takasu, Fugo
Abstract: In avian brood parasitism, both the host and the parasite are expected to develop various conflicting adaptations; hosts develop a defense against parasitism, such as an ability to recognize and reject parasitic eggs that look unlike their own, while parasites evolve egg mimicry to counter this host defense. Hosts may further evolve to generate various egg phenotypes that are not mimicked by parasites. Difference in egg phenotype critically affects the successful reproduction of hosts and parasites. Recent studies have shown that clear polymorphism in egg phenotype is observed in several host–parasite interactions, which suggests that egg polymorphism may be a more universal phenomenon than previously thought. We examined the mechanism for maintaining egg polymorphism in the rufescent prinia ( Prinia rufescens ) that is parasitized by the plaintive cuckoo ( Cacomantis merulinus ) from a theoretical viewpoint based on a mathematical model. The prinia has four distinct egg phenotypes: immaculate white, immaculate blue, white with spots, and blue with spots. Only two egg phenotypes, white with spots and blue with spots, are found in the cuckoo population. We show that the observed prinia and cuckoo phenotypes cannot be at an equilibrium and that egg polymorphism can be maintained either at stationary equilibrium or with dynamic, frequency oscillations, depending on the mutation rates of the background color and spottiness. Long‐term monitoring of the prinia–cuckoo interaction over a wide geographic range is needed to test the results of the model analyses. Abstract : We study egg polymorphism of the rufescent prinia and the plaintive cuckoo where distinct four types of eggs are observed in the prinia but only two are found in the cuckoo. We study how this egg polymorphism can be maintained using a mathematical model.